PENGARUH PREDNISON TERHADAP PERBAIKAN PENDENGARAN PENDERITA LUPUS ERITEMATOSUS - Wijana, Wijana; Mutiara, Ira Agustine; Agustian, Ratna Aggraeni (Majalah Kedokteran Bandung, 2016)
Lupus eritematosus sistemik (LES) merupakan penyakit kronik mengenai multisistem, merupakan gangguan autoimun yang ditandai oleh produksi autoantibodi dan deposisi kompleks imun di jaringan. Manifestasi klinis dapat meliputi berbagai organ termasuk telinga. Pada telinga dapat menimbulkan gangguan dengar, tinitus, dan vertigo. Gangguan dengar terjadi bilateral pada frekuensi tinggi. Prednison merupakan kortikosteroid oral yang memiliki efek glukokortikoid yang bersifat anti-inflamasi dan imunosupresif. Penelitian ini bertujuan mengetahui pengaruh prednison terhadap perbaikan pendengaran penderita LES. Penelitian dilakukan periode Maret?Mei 2013 di Poliklinik Gangguan Dengar dan Bicara, Telinga Hidung Tenggorok Bedah Kepala dan Leher Rumah Sakit Dr. Hasan Sadikin Bandung menggunakan metode quasi-experimental dengan rancangan one group pretest-posttest design dan hasilnya dihitung secara statistik menggunakan uji Rank Spearman. Pada 28 subjek pasien LES dilakukan anamnesis, pemeriksaan fisis, laboratorium, audiometri nada murni, timpanometri, dan distortion production otoacoustic emissions. Subjek diberi prednison 1 mg/kgBB/hari (dosis maksimal 60 mg/hari) selama 4 minggu, kemudian dilakukan evaluasi ulang. Sebelum terapi, 26 subjek mengalami gangguan dengar sedang pada frekuensi tinggi, simetris. Sesudah terapi, 24 subjek ambang dengar menjadi normal dan 4 subjek tetap mengalami gangguan dengar (Rs=0,734; p<0,01). Simpulan, prednison dapat memperbaiki status pendengaran penderita LES.  [MKB. 2016;48(2):112?7]Kata kunci: Gangguan dengar, lupus eritematosus sistemik, prednisonPrednisone Effect to on Hearing Status of Systemic Lupus Erythematosus PatientsSystemic lupus erythematosus (SLE) is a chronic, multi-system, autoimmune disorder characterized by the production of autoantibodies and immune complexes deposition in tissue. Clinical manifestations may include skin, mucosa, joints, blood, heart, lungs, kidneys, central nervous system (CNS), immune system, and ears. SLE Iin the ears can caused sensorineural hearing loss, tinnitus, and vertigo. This hearing disorder is commonly bilateral and has high frequencies. Prednisone is an oral corticosteroid with glucocorticoid and mineralocorticoid effects. Glucocorticoids have anti-inflammatory and immunosuppressive effects. The aim of this study was to evaluate the effect of prednisone in improving the degree of hearing loss in patients with SLE. This study was conducted in from March?May 2013, at tThe Hearing and Speech Disorder Clinic of Ear Nose Throat-Head and Neck Surgery, Dr. Hasan Sadikin Hospital Bandung, using quasi-experimental method with pre-post design in which the results were statistically calculated using Rank Spearman test. This study involved 28 subjects who had been diagnosed for SLE. Anamnesis, physical examination, and laboratory test were performed, followed by pure tone audiometry, tympanometry, and distortion product optoacoustic emissions (DPOAE). Subjects were given prednisone 1 mg/kgBW/day with a maximum dose of 6o mg/day. Re-evaluation was performed after 4 weeksof treatment. Before treatment, 26 subjects had mild hearing loss and 2 subjects had symmetric moderate hearing loss at high frequencies symmetrically. After therapy, 24 subjects became normal and 4 subjects still had hearing loss (Rs=0.734, p<0.01). In conclusion, prednisone can improve hearing status of SLE patients. [MKB. 2016;48(2):112?7]Key words: Hearing loss, prednisone, systemic lupus erythematosus DOI: 10.15395/mkb.v48n2.765